2013
DOI: 10.3389/fendo.2013.00016
|View full text |Cite
|
Sign up to set email alerts
|

Linagliptin: A thorough Characterization beyond Its Clinical Efficacy

Abstract: Linagliptin, one of the five dipeptidyl peptidase-4 inhibitors available, has recently entered the market both in the US and in most European countries for treatment of type 2 diabetes mellitus. It presents a xanthine-based structure, and is characterized by unique pharmacokinetics, with non-linear profile, long terminal half-life allowing prolonged exposure to the drug. It is eliminated predominately through the intestinal tract and only minimally into urine, so that it can be administered, without any dose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 54 publications
0
15
0
Order By: Relevance
“…Linagliptin, a third approved DPP-4 inhibitor for diabetes [12], has previously been shown to reduce infarct size and lipid oxidation after ischemia in an isolated heart preparation [32] as well as inhibit inflammation and immune response in the atherosclerotic state [33]. Phase 3 clinical trials have also provided valuable new insights in the cardiovascular safety profile to show the benefits of linagliptin in patients with type 2 diabetes [34]. In the present study, we found that oral administration of linagliptin on a daily basis inhibits Ang IIinduced cardiac fibrosis without showing any side-effects, suggesting that preservation of endogenous GLP-1 is as effective as an exogenous supply of GLP-1 in attenuating cardiac injury.…”
Section: Discussionmentioning
confidence: 99%
“…Linagliptin, a third approved DPP-4 inhibitor for diabetes [12], has previously been shown to reduce infarct size and lipid oxidation after ischemia in an isolated heart preparation [32] as well as inhibit inflammation and immune response in the atherosclerotic state [33]. Phase 3 clinical trials have also provided valuable new insights in the cardiovascular safety profile to show the benefits of linagliptin in patients with type 2 diabetes [34]. In the present study, we found that oral administration of linagliptin on a daily basis inhibits Ang IIinduced cardiac fibrosis without showing any side-effects, suggesting that preservation of endogenous GLP-1 is as effective as an exogenous supply of GLP-1 in attenuating cardiac injury.…”
Section: Discussionmentioning
confidence: 99%
“…In 20 certain instances specific peptide sequences have been linked with DPP-IV inhibition 94,[101][102][103][104][105] . Milk protein-derived DPP-IV inhibitory peptides generally have an IC 50 value in the µM range 28 , which is several orders of magnitude higher than that of gliptins (nM) 106 . To date, four in vivo studies have demonstrated 25 that food protein hydrolysates or peptides with in vitro DPP-IV inhibitory properties were able to induce an increased insulin secretion and a reduction in plasma glucose following an oral glucose tolerance test in rodents.…”
Section: Peptidesmentioning
confidence: 98%
“…Their use is particularly advantageous since they induce low rates of hypoglycemia and are considered weight neutral (DPP4 inhibitors) or can even induce weight loss (GLP1 analogs) [89]. In addition, the large distribution of DPP4 and its pleiotropic effects make this molecule an attractive target for therapeutic intervention beyond the classical use of DPP4 inhibitors as antiglycemic agents [90].…”
Section: Dipeptidyl Peptidase 4 (Dpp4) Inhibitorsmentioning
confidence: 99%